Analisis Faktor Keunggulan Bersaing Logistik Berbasis Digital pada Perusahaan J&T di Wilayah Purwakarta - Lintang Lintang; Andi Mezzaluna Kirani; Muhammad Agung Fadillah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to identify the sub-factors of digital-based logistics competitive advantage at PT J&T Express in Purwakarta Regency. This suburban area possesses unique geo-economic characteristics that challenge the company's supply chain digitalization capabilities. Data collection was conducted quantitatively through structured questionnaires distributed to 81 service users. Data analysis was completed using an integrative method of Exploratory Factor Analysis (EFA) for dimensional reduction and path regression analysis assisted by SmartPLS 4. Empirical results indicate that among the six sub-factors, only Factor 2  (Tariff Effectiveness) proved to have a positive and significant effect on Competitive Advantage with a path coefficient of 0.428 and a P-value of 0.001. The other five macro-technology sub-factors were insignificant because the suburban market is more price-sensitive and values basic reliability over complex features.